Differential effects in CGRPergic, nitrergic, and VIPergic myenteric innervation in diabetic rats supplemented with 2% L-glutamine - RENATA V.F. PEREIRA; DAVID R. LINDEN; MARCÍLIO H. MIRANDA-NETO; JACQUELINE N. ZANONI (Anais da Academia Brasileira de Ciências, 2016)
ABSTRACT The objective of this study was to investigate the effects of 2% L-glutamine supplementation on myenteric innervation in the ileum of diabetic rats, grouped as follows: normoglycemic (N); normoglycemic supplemented with L-glutamine (NG); diabetic (D); and diabetic supplemented with L-glutamine (DG). The ileums were subjected to immunohistochemical techniques to localize neurons immunoreactive to HuC/D protein (HuC/D-IR) and neuronal nitric oxide synthase enzyme (nNOS-IR) and to analyze varicosities immunoreactive to vasoactive intestinal polypeptide (VIP-IR) and calcitonin gene-related peptide (CGRP-IR). L-Glutamine in the DG group (i) prevented the increase in the cell body area of nNOS-IR neurons, (ii) prevented the increase in the area of VIP-IR varicosities, (iii) did not prevent the loss of HuC/D-IR and nNOS-IR neurons per ganglion, and (iv) reduced the size of CGRP-IR varicosities. L-Glutamine in the NG group reduced (i) the number of HuC/D-IR and nNOS-IR neurons per ganglion, (ii) the cell body area of nNOS-IR neurons, and (iii) the size of VIP-IR and CGRP-IR varicosities. 2% L-glutamine supplementation exerted differential neuroprotective effects in experimental diabetes neuropathy that depended on the type of neurotransmitter analyzed. However, the effects of this dose of L-glutamine on normoglycemic animals suggests there are additional actions of this beyond its antioxidant capacity.